The scandalous Gospel of Jesus : what's so good about the good news? - Gomes, Peter J. (USA: Harper One , An Imprint of Harper Collins Publication, 2007)
Addresses key issues in the modern church and explores the dangers of focusing excessively on the Bible, in a spiritual resource that seeks to illuminate what the author believes to be Jesus's original transformative and revolutionary message of hope.
The trouble with Scripture -- The Gospel and the conventional wisdom -- Where do we go from here?
Includes bibliographical references (pages 249-251) and index.
Keywords: Jesus Christ -- Person and offices; Apologetics; Spirituality